2003
DOI: 10.1242/jeb.00422
|View full text |Cite
|
Sign up to set email alerts
|

The role of eukaryotic initiation factor 2α during the metabolic depression associated with estivation

Abstract: During adverse environmental conditions, many organisms are able to enter a state of quiescence and survive for extended periods on stored fuels. Associated with this quiescence there is typically a depression of basal metabolic rate by 60-100% (termed metabolic depression; Guppy and Withers, 1999), which necessitates a coordinated change in ATP production and utilization. Estivation is a form of metabolic depression that occurs in some animals in response to a lack of food and/or water or in response to other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 34 publications
1
6
0
1
Order By: Relevance
“…2.2) and foot muscle showed a 20-fold higher P-eIF2a (Ser51) content after 14 days (Ramnanan et al 2009). Pakay et al (2003) also found a approximately twofold increase in the relative amount of P-eIF2a in liver extracts from aestivating desert frogs (Neobatrachus sutor), but in H. aspersa the amount of P-eIF2a was below the detection limit in hepatopancreas of both aestivating and awake snails (Pakay et al 2003).…”
Section: Protein Synthesismentioning
confidence: 98%
“…2.2) and foot muscle showed a 20-fold higher P-eIF2a (Ser51) content after 14 days (Ramnanan et al 2009). Pakay et al (2003) also found a approximately twofold increase in the relative amount of P-eIF2a in liver extracts from aestivating desert frogs (Neobatrachus sutor), but in H. aspersa the amount of P-eIF2a was below the detection limit in hepatopancreas of both aestivating and awake snails (Pakay et al 2003).…”
Section: Protein Synthesismentioning
confidence: 98%
“…Phosphorylation of eIF2 blocks the protein from being recharged with GTP and thereby inhibits its GTP-dependent function in the delivery and attachment of the initiating methionine residue to the assembling ribosome (Proud, 2007). Phosphorylated eIF2 content also increased in liver of aestivating desert frogs (Pakay et al, 2003). The eIF4 complex is regulated at several points.…”
Section: Growth And/or Development Signaling: Akt and Mtormentioning
confidence: 99%
“…Thus, low levels of eIF2α and/or elevated expression of p-eIF2α indicate suppression of the protein synthesis in the muscles of P. diplolister during aestivation. The stable level of eIF2α and p-eIF2α in the other studied P. diplolister muscles might indicate that the regulation of the protein synthesis in these tissues might be dependent on alternative mechanisms such as control of the translation elongation [38] or ribosome (dis)assembly [39]. Suppression of the protein synthesis is a common energy-saving mechanism in estivating species [38] and has been observed in desert amphibians Neobatrachus centralis [40] and in estivating snails Otala lactea [41,42].…”
Section: Discussionmentioning
confidence: 99%
“…The stable level of eIF2α and p-eIF2α in the other studied P. diplolister muscles might indicate that the regulation of the protein synthesis in these tissues might be dependent on alternative mechanisms such as control of the translation elongation [38] or ribosome (dis)assembly [39]. Suppression of the protein synthesis is a common energy-saving mechanism in estivating species [38] and has been observed in desert amphibians Neobatrachus centralis [40] and in estivating snails Otala lactea [41,42]. Earlier studies on estivating frogs ( Cyclorana alboguttata) showed that muscles are protected against atrophy during prolonged (9 months) estivation with no decline in muscle mass, cross-sectional area or fiber number [7].…”
Section: Discussionmentioning
confidence: 99%